Activity of metallurgical enterprises East and South of Ukraine in 1917–1918 - Syniavska, L. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. The revolutionary events of 1917 significantly affected on the organization of the metallurgical enterprises. Under the pressure of economic problems the volume of manufactured products began to decrease. The relationship between industrialists and employees began increasingly exacerbated. Purpose. To analyze the activity of metallurgical enterprises of the East and South of Ukraine with the definition of circumstances that influenced on the volume of manufactured products. Results. It is proved that the greatest decline in production was observed in 1917–1918 when the unstable political and economic situation negatively affected on the development of the metallurgical enterprises of the East and South of Ukraine. Originality. The influence of workers’ committees in the organization of the metallurgical enterprises is determined. The importance of transport infrastructure to ensure smooth transportation of steel products is showed. Conclusion. Reduction of iron smelting was observed immediately after the overthrow of the autocracy and changes the system of government that pulled the destruction of industrial relations and a sharp reduction in the number of skilled managers’ enterprises. Workers’ committees could not replace the management positions experienced administrators. Intervention of workers in the course of the production process had a negative impact on manufacturing output. At many enterprises were violated technological cycles, destroyed documents, lost technical staff. Much of metallurgical enterprises completely stopped working with stopping blast furnaces, the launch of which has become extremely difficult.